Who gets a mammogram amongst European women aged 50-69 years? - Ansgar Wuebker (Health Economics Review, 2012)
On the basis of the Survey of Health, Ageing, and Retirement (SHARE), we analyse the determinants of who engages in mammography screening focusing on European women aged 50-69 years. A special emphasis is put on the measurement error of subjective life expectancy and on the measurement and impact of physician quality. Our main findings are that physician quality, better education, having a partner, younger age and better health are associated with higher rates of receipt. The impact of subjective life expectancy on screening decision substantially increases after taking measurement error into account.
Keywords: C36; I11; I18; 330; mammogram; physician quality; life expectancy; instrumental variables; Krebskrankheit; Gesundheitsvorsorge; Frauen; Sterblichkeit; Europa